Estrategias integradas para control de la broca (Hypothenemus hampei) en plantaciones de café (Coffea arabica L), en el cantón Sozoranga, provincia de Loja - Catota Arrobo, Víctor Geovanny (2022)
In Ecuador, coffee (Coffea arabica) productions are representative in the economy of the national agricultural sector, traditionally producing two species of coffee (Arabica and Robusta), Loja is the second province with the largest coffee surface in the country, highlighting that 75 % of the coffees are in the localities of Loja, Olmedo, Sozoranga, Quilanga and Chaguarpamba, according to reports it is estimated that national production is reduced in average terms due to the presence of pests and diseases by 58 %, with Hypothenemus hampei being the pest positioned as the one of greatest economic importance in the cultivation of coffee and in the southern region of Ecuador. That is why it was proposed to validate a proposal for the Integrated Management of the coffee borer (Hypothenemus hampei). The trial was carried out in an Arabica coffee producing farm located in the Sozoranga canton of Loja province. It was established under a Completely Random Block Method, with seven treatments and four repetitions. The variables evaluated were number of healthy grains, number of brocaded grains, incidence index, severity index. In the case of brocaded grains, the number of eggs, larvae, pupae and adults of coffee borer were evaluated. The effect of the treatments on the dependent variables was evaluated by means of ANOVA and the test of means (Tukey) (p = 0.05). The results show that in most of the variables significant differences were found between treatments. However, the chemical control treatments, the two botanical and biological extracts, presented the best results in controlling CBB. In general, the results of this work show that the different treatments produce a significant effect on the population reduction of Hypothenemus hampei. In this sense, and based on the results, it is suggested that three of the four components used (biological, ethological traps and botanical extracts) be used as a priority in association, to obtain greater efficiency in controlling CBB on coffee plantations, and avoid in chemical control as possible. Key words: Coffea arabica, Hypothenemus hampei, ethological traps, botanical extracts, biological control, chemical control, integrated management.